Case linkage in Australian serial stranger rape. Issue 1 (23rd July 2020) - Davidson, Serena; Petherick, Wayne
Abstract : Purpose: Case linkage theory and practice have received growing empirical support; however, they have yet to be examined fully within Australia. For sexual assault case linkage to be successful, it is assumed that a serial rapist will behave relatively consistently across offences yet distinctively compared to other offenders. The purpose of this paper is to test the underlying principles of case linkage, behavioural consistency and distinctiveness, as well as distinguishing accuracy. Design/methodology/approach: In total, 250 solved stranger rapes by 171 offenders (46 serial rapists, 125 one-off rapists) were taken from Queensland Police Service (QPS) crime records. All possible crime pairings were created and cross-crime similarity was assessed using Jaccard's coefficient. Receiver operating characteristics (ROC) analysis was used to examine the ability to distinguish between linked and unlinked offence pairs. Findings: Serial linked pairs had the highest Jaccard's coefficient (0.456), followed by non-serial unlinked (0.253) and finally, serial unlinked pairs (0.247). Within the ROC analysis, an area under the curve value was found of 0.913, indicating excellent distinguishing accuracy. Both the underlying principles of behavioural consistency and distinctiveness were supported through theoretical and practical methods. This paper provides the first analysis of serial rape case linkage in Australia, adding validity to this practice. Research limitations/implications: The authors wish to acknowledge the support and assistance from the QPS in undertaking this research. The views expressed in this publication are not necessarily those of the QPS and any errors of omission or commission are the responsibility of the authors. Practical implications: This paper provides validity to the practice of case linkage using a database within Australia. The results of this paper can be used to inform investigators of serial offender behaviours. The theories of offender consistency and distinctiveness are supported, highlighting the importance of behavioural evidence for practitioners. This paper provided a practical increase of the quantity and quality of offences uploaded on the Australian violent and sexual crimes database, which will assist further linkage efforts. Originality/value: This paper is the first in Australia to examine consistency, distinctiveness and case linkage of serial stranger rape. Thus is contributes significantly not only to an increased understanding of serial rape and case linkage in Australia but also brings Australia closer to modern research practices in this field.